THE CORRELATION BETWEEN SEMANTIC AND PHONOLOGY - Nurul Hidayati (Universitas 17 Agustus 1945 Semarang, 2020)
Semantic is the study of meaning communication through language. Linguist who work in these branches of linguistics are interested in the ways in which words acquire meaning and the processes by which native users of a language are able to give stable interpretations to word strings. Problems of meaning are arguably among the most significant which addressers and addressees experience in communicating with the other. This is principally because of two things: first, the range of possible meanings of which many words are capable; and second, the considerable contextual features which influence how strings are interpreted. We are all aware, in everyday communication, just how much factors such as intonation, word stress, and situational context can affect the interpretation of utterances. In the other hand, phonology is defined about the speech on sound including intonation and stress. This paper describes that semantic and phonology have the correlation in analyzing the language communication. Keywords: Correlation, Semantic, and Phonology.